Purification and primary structure of a mannose/glucose‐binding lectin from Parkia biglobosa Jacq. seeds with antinociceptive and anti‐inflammatory properties. Issue 10 (29th August 2013) - Silva, Helton C.; Bari, Alfa U.; Rocha, Bruno Anderson M.; Nascimento, Kyria S.; Ponte, Edson L.; Pires, Alana F.; Delatorre, Plínio; Teixeira, Edson H.; Debray, Henri; Assreuy, Ana Maria S.; Nagano, Celso S.; Cavada, Benildo S.
<x xml:space="preserve">Abstract</x> Parkia biglobosa (subfamily Mimosoideae), a typical tree from African savannas, possess a seed lectin that was purified by combination of ammonium sulfate precipitation and affinity chromatography on a Sephadex G‐100 column. The P. biglobosa lectin (PBL) strongly agglutinated rabbit erythrocytes, an effect that was inhibited by d‐mannose and d‐glucose‐derived sugars, especially α‐methyl‐d‐mannopyranoside and N‐acetyl‐d‐glucosamine. The hemagglutinating activity of PBL was maintained after incubation at a wide range of temperature and pH and also was independent of divalent cations. By sodium dodecyl sulfate–polyacrylamide gel electrophoresis analysis, PBL exhibited an electrophoretic profile consisting of a single band with apparent molecular mass of 45 kDa. An analysis using electrospray ionization–mass spectrometry indicated that purified lectin possesses a molecular average mass of 47 562 ± 4 Da, and the analysis by gel filtration showed that PBL is a dimer in solution. The complete amino acid sequence of PBL, as determined using tandem mass spectrometry, consists of 443 amino acid residues. PBL is composed of a single non‐glycosylated polypeptide chain of three tandemly arranged jacalin‐related domains. Sequence heterogeneity was found in six positions, indicating that the PBL preparations contain highly homologous isolectins. PBL showed important antinociceptive activity associated to the inhibition of inflammatory process. Copyright © 2013 John Wiley & Sons, Ltd.